2022
DOI: 10.3389/fmicb.2022.863624
|View full text |Cite
|
Sign up to set email alerts
|

Phillygenin Inhibits Helicobacter pylori by Preventing Biofilm Formation and Inducing ATP Leakage

Abstract: With the widespread use and abuse of antibiotics, Helicobacter pylori (H. pylori) has become seriously drug resistant. The development of new antibiotics is an important way to solve H. pylori's drug resistance. Screening antibacterial ingredients from natural products is a convenient way to develop new antibiotics. Phillygenin, an effective antibacterial component, was selected from the natural product, forsythia, in this study. Its minimal inhibitory concentration (MIC) for 18 H. pylori strains was 16–32 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The relationship between H. pylori biofilm formation and antibiotic resistance requires further study. In addition, new drugs for H. pylori biofilm intervention have recently emerged, such as nanomaterials, Chinese herbal extracts, and probiotics [ [40] , [41] , [42] , [43] , [44] , [45] ], but the mechanism by which they reduce H. pylori biofilm formation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between H. pylori biofilm formation and antibiotic resistance requires further study. In addition, new drugs for H. pylori biofilm intervention have recently emerged, such as nanomaterials, Chinese herbal extracts, and probiotics [ [40] , [41] , [42] , [43] , [44] , [45] ], but the mechanism by which they reduce H. pylori biofilm formation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, new drugs for helicobacter pylori bio lm intervention have emerged in large numbers recently, such as nanomaterials, chinese herbal extracts, probiotics, etc. [38][39][40][41][42] Helicobacter bio lm remained a niche eld of study. More and more study occurred in recent 5 years, although its IF was not high, it is meaningful for long-term academic development in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 10 categories of antibacterial mechanism were examined in the studies: (1) antibiofilm, (2) anti-urease, (3) gastroprotection, (4) anti-inflammation, (5) effect on H. pylori virulence factors, (6) ATP leakage from H. pylori, (7) immune response, (8) H. pylori conversion from spiral to coccoid (inactive form), (9) cellular signaling, and (10) bacterial burden. Two studies found that the ethyl acetate fraction from Hibiscus rosa-sinensis red flower [29] and phylligenin, a compound isolated from flowering plant Forsythia [37], exhibited anti-biofilm activity against H. pylori. Meanwhile, four studies found that natural plant products possessed anti-urease activity, and six studies showed the gastroprotective properties of plant natural products.…”
Section: Antibacterial Activity Of Natural Products From Plants and N...mentioning
confidence: 99%
“…Two studies each demonstrated a reduction in cellular signaling important in H. pylori-induced carcinogenesis [30,48] and conversion of H. pylori from the active (spiral) to inactive coccoid form [29,42]. Li et al [37] observed that phylligenin extracted from Forsythia induced ATP leakage in H. pylori and inhibited the mechanism of antibacterial resistance in the bacteria, as well as induced a good immune response.…”
Section: Antibacterial Activity Of Natural Products From Plants and N...mentioning
confidence: 99%